Improvement of pre-service teachers' practical knowledge and motivation about artificial intelligence through a service-learning-based module in Guizhou, China: a quasi-experimental study / Song Pu ... [et al.] - Pu, Song; Ahmad, Nor Aniza; Md. Khambari, Mas Nida; Yap, Ng Keng; Ahrari, Seyedali (Universiti Teknologi MARA, 2021)
The purpose of this study is twofold: 1) to develop a service-learning-based module training artificial intelligence (AI) subject (SLBM-TAIS), and 2) to evaluate the effect of SLBM-TAIS on pre-service teachers' (PSTs') practical knowledge and motivation, as well as primary school students' attitude towards AI in China. Participants of this study comprised 60 PSTs and 107 primary school students. The experimental research in this study followed the quasi-experimental non-randomized pre-test and post-test control group design. The PSTs were divided into experimental and control groups, and the primary school students followed the same grouping. The PSTs in the experimental group taught AI subjects to the primary school students in the experimental group, while the PSTs in the control group taught AI subjects to the primary school students in the control group. The results of the study showed that SLBM-TAIS was effective in training PSTs to teach AI subjects to primary school students. Furthermore, the SLBM-TAIS developed in this study offered a unique technique for training PSTs and primary school students that could increase PSTs' practical knowledge and motivation, as well as primary school students' attitudes toward AI. The findings from this study are important in the field of educational psychology, and its contribution has several theoretical and practical implications.